Analisis Pengelolaan Barang Milik Daerah Pada Dinas Perhubungan Provinsi Sumatera Utara - Amaluddin Siregar; Nurlinda; Meily Surianti (PERSEPTIF: Jurnal Ilmu Sosial dan Humaniora, 2026)
The management of Regional Property at the Transportation Office of North Sumatra Province faces significant challenges in ensuring the effectiveness and efficiency of regional assets. This study aims to analyze key aspects of BMD management, including planning, utilization, utilization, security, and administration of assets within the Transportation Office. The research method used is interviews with relevant officials and document analysis, which reveals discrepancies between planning and budgeting, suboptimal management, and administrative issues that hinder management efficiency. Several key assets were also found to be idle, potentially causing losses for the region. From these findings, the study recommends improving coordination between the Transportation Office, BPKAD, and TAPD, as well as enhancing the quality of human resources involved in the management of Regional Property. The implementation of a more integrated system and improved compliance with existing regulations are expected to address the challenges and improve the overall performance of regional asset management. The results of this study are expected to contribute to improving the governance of The management of Regional Property, both for the Transportation Office of North Sumatra Province and for other agencies facing similar challenges.